2022
DOI: 10.1039/d1cp05660c
|View full text |Cite
|
Sign up to set email alerts
|

Halogen and structure sensitivity of halobenzene adsorption on copper surfaces

Abstract: The adsorption orientation of molecules on surfaces influences their reactivity, but it is still challenging to tailor the interactions that govern their orientation. Here, we investigate how the substituent and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…To limit the monolayer coverage condition, a small (4 × 4) Cu(111) cell was used. The coverage of this unit cell corresponds to 1.1 monolayer (1.1 molecules per nm 2 ), which is approximately the highest molecule density for parallel adsorbed aryl halides if all molecules adopted equivalent adsorption sites . For comparison, a (3 × 3) Cu(111) cell would make the iodine atoms of 1,3,5-triiodobenzne too close (1.4–2.8 Å) to each other and lead to a tilted absorption configuration on Cu(111).…”
Section: Methodsmentioning
confidence: 99%
“…To limit the monolayer coverage condition, a small (4 × 4) Cu(111) cell was used. The coverage of this unit cell corresponds to 1.1 monolayer (1.1 molecules per nm 2 ), which is approximately the highest molecule density for parallel adsorbed aryl halides if all molecules adopted equivalent adsorption sites . For comparison, a (3 × 3) Cu(111) cell would make the iodine atoms of 1,3,5-triiodobenzne too close (1.4–2.8 Å) to each other and lead to a tilted absorption configuration on Cu(111).…”
Section: Methodsmentioning
confidence: 99%
“…The replacement of the isopropyl groups with hydrogen atoms is not expected to cause major wavenumber vibrational differences in the whole of TIPS-Pc given that differently functionalized halobenzenes adsorbed to surfaces possess only minor IR vibrational energy differences (less than 20 cm −1 in C−C stretches and less than 10 cm -1 in C−H stretches). 55 In all other surface−adsorbate calculations, a full four-layer Au(111) surface and TIPS-Pc with its isopropyl groups were used.…”
Section: ■ Methodsmentioning
confidence: 99%
“…In the IR and Raman calculations, the isopropyl groups of TIPS-Pc were modeled using hydrogen atoms to reduce the computational cost, and the Au surface was removed, except for the Au atoms forming Au–C bonds in the chemisorbed system. The replacement of the isopropyl groups with hydrogen atoms is not expected to cause major wavenumber vibrational differences in the whole of TIPS-Pc given that differently functionalized halobenzenes adsorbed to surfaces possess only minor IR vibrational energy differences (less than 20 cm –1 in C–C stretches and less than 10 cm ‑1 in C–H stretches) . In all other surface–adsorbate calculations, a full four-layer Au(111) surface and TIPS-Pc with its isopropyl groups were used.…”
Section: Methodsmentioning
confidence: 99%
“…61 Furthermore, Schunke et al investigated the influence of the adsorption orientation of halobenzene on copper surfaces via infrared spectroscopy experiments. 32 In this work, frequency calculations have been performed to simulate the vibrational IR spectra of the isolated molecules and the complexes, and to investigate how the interaction with GNP affects the IR spectra. This insight would be helpful to structural identification in experimental IR spectra.…”
Section: Vibrational Analysismentioning
confidence: 99%
“…However, previous studies of aromatic containing compounds deposited on metal surfaces have indicated that the aromatic plane is not always adsorbed in a parallel configuration. 8,12,13,32 They could adopt either a perpendicular configuration or a tilted orientation with respect to the plane of the surface. Contributing factors include, among others, the presence of functional groups, that either alter the electron density of the aromatic compound, introduce steric effects or lead to stronger ''direct'' interactions because of high ligand affinity for gold.…”
Section: Introductionmentioning
confidence: 99%